A Practitioners’ Mutual Aid Group: Connection and Leadership During the Pandemic - Beno, Mary Frances H; Casstevens, Willa J; Godfrey-Kaplan, Será; Karroumi, Moe; Letendre, Joan; Meir, Lynn; Tevik, Kelsey; Weliky, Deirdre (Groupwork, 2025)
This article focuses on group leadership during times of crisis, using an example of a social work practitioners’ mutual aid group formed during the second year of the Covid-19 pandemic in the United States. As the group learned, external crises change over time and this can impact group formation and the development of mutual aid, as well as leadership. We observed that group leadership supported group participants to and through Bolsinger’s (2020) adaptive phase of development during the pandemic and its associated personal stressors. This occurred during the storming – and into the norming – stages of the group (Tuckman, 1965; Bonebright, 2010). Ongoing participant reflection and group meta-reflection yielded broader understanding of interactions between stages of group development, and phases of crisis. In addition, it highlighted an associated need for flexible leadership that is sensitive to the changing external stressors during times of social or environmental crisis. Such leadership can also undergird the development of mutual aid among group participants, an important consideration at any time.